2014
DOI: 10.1186/s13023-014-0161-1
|View full text |Cite
|
Sign up to set email alerts
|

Three new cases of late-onset cblC defect and review of the literature illustrating when to consider inborn errors of metabolism beyond infancy

Abstract: BackgroundThe cblC defect is a rare inborn error of intracellular cobalamin metabolism. Biochemical hallmarks are elevated homocysteine and low methionine in plasma accompanied by methylmalonic aciduria. Due to the heterogeneous clinical picture, patients with the late-onset form of the disease (onset >12 months) come to the attention of diverse medical specialists, e.g. paediatricians, neurologists, nephrologists, psychiatrists or haematologists. The report reviews the published clinical data and adds three n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
0
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(135 citation statements)
references
References 42 publications
7
114
0
14
Order By: Relevance
“…The overall disease load did not increase as significantly over time as in the very low activity group and mortality was less; this finding corresponds with the observations in the late-onset cblC defect (Huemer et al 2014b).…”
Section: Discussionsupporting
confidence: 86%
“…The overall disease load did not increase as significantly over time as in the very low activity group and mortality was less; this finding corresponds with the observations in the late-onset cblC defect (Huemer et al 2014b).…”
Section: Discussionsupporting
confidence: 86%
“…2). Cases presenting with aHUS that are rescued by hydroxocobalamin treatment appear to be at least as frequent in late-onset cblC defect as in neonatal forms [29][30][31][32][33][34] (Table 1).…”
Section: Diagnosis Of Atypical Husmentioning
confidence: 99%
“…Biological assays to confirm the clinical diagnosis of aHUS In children, clinical presentation and baseline laboratory results usually allow the diagnosis of Streptococcus pneumoniae, STEC and cobalamin C (cblC) defect-HUS or of TTP with a good degree of certainty to inform adequate treatment initiation (Table 1) [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Figure 2 outlines confirmatory investigations for each of the common differential diagnoses [35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Diagnosis Of Atypical Husmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Among patients with cbl-C disorder, HUS has been reported in white children. [8][9][10] In addition, recent studies [11,12] have reported that approximately 10% of patients with cbl-C disorder develop HUS and the occurrence of HUS is at least as frequent in late forms of cbl-C defect as in neonatal forms. [11] In the present report, we presented with clinical characteristics of 3 Chinese children with HUS secondary to cbl-C disorder.…”
Section: Introductionmentioning
confidence: 97%